ANALISIS EMPLOYEE ENGAGEMENT, KOMITMEN ORGANISASI, DAN ROTASI KERJA TERHADAP KINERJA - Yolanda Irfania; Hesty Prima Rini (JURNAL LENTERA BISNIS, 2025)
Every organization wants to have employees with work results that continue to increase. If there is an increase in employee performance, it will have a good impact on organizational performance. The purpose of this study is to understand the effect of employee engagement, organizational commitment, and job rotation on employee performance. The population and sample used were 47 employees of BKPSDM Pamekasan Regency. Data were obtained through distributing questionnaires and processed by utilizing Smart Partial Least Square (SmartPLS) software. This study proves that the level of employee performance is positively influenced by employee engagement, organizational commitment, and job rotation on employee performance. Employees who have a sense of attachment, uphold commitment in the organization, and have a high chance of rotation will make the performance deployed by employees increase.